A Study Of The Social Determinants Of Infant Mortality In Malaysia - Ahmad, A. (2008)
This study comprises an ecological (area-based) population health survey involving all 135 administrative districts of Malaysia. A literature review was undertaken in order to develop a model that hypothesises the main social determinants of infant mortality in Malaysia. In order to test the model, secondary cross-sectional data from a range of sources were collected and analysed. Statistical analysis of the data using general linear model including correlations, factor analysis and multiple regression were undertaken in order to examine the collective influence of a range of social factors on variations observed in infant mortality. Determinants of infant mortality in Malaysia tested in this study include GDP per capita, poverty rate, mean income of bottom 40% income earner, Gini coefficient, ratio of top 20% income: to bottom 40% income, population per doctor ratio, hospital bed per population ratio, car ownership per population, computer ownership per population, urbanization rate, percentage living in single housing and flats, women education and social development index.